Molecular networking-based for the target discovery of potent antiproliferative polycyclic macrolactam ansamycins from Streptomyces cacaoi subsp. asoensis. Issue 24 (2nd September 2020) - Liu, Ling-Li; Chen, Zhi-Fan; Liu, Yao; Tang, Dan; Gao, Hua-Hua; Zhang, Qiang; Gao, Jin-Ming
Abstract : Molecular networking-based for the target discovery of potent antiproliferative polycyclic macrolactam ansamycins. Abstract : To find bioactive natural products, the ethyl acetate extract of Streptomyces cacaoi subsp. asoensis H2S5 was analyzed based on molecular networking. The analysis targeted a specific cluster and led to the discovery of two unprecedented rearranged ansamycins incorporating a fused 5/6/7 tricyclic ring system, strecacansamycins A (1 ) and B (2 ), and one rare glycosylated trienomycin, strecacansamycin C (3 ). Their structures were determined by comprehensive NMR analysis, ECD calculations, chemical reactions, and enzyme stereospecificity analysis. The genome of the produced strain was sequenced and the related gene cluster ( tym ) was identified. With the availability of the genome sequence data, the known stereospecificities of biosynthetic enzymes provided more evidence for the absolute stereochemistry identification. Anti-proliferative assays revealed that strecacansamycin A (1 ) exhibited significant activity with the IC50 values of 2.21, 0.61, and 7.01 μM against PC-3, HepG2, and U87-MG cells, respectively.